2009
DOI: 10.1099/mic.0.033175-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a non-invasive murine infection model for acute otitis media

Abstract: Otitis media (OM) is one of the most frequent diseases in childhood, and Streptococcus pneumoniae is among the main causative bacterial agents. Since current experimental models used to study the bacterial pathogenesis of OM have several limitations, such as the invasiveness of the experimental procedures, we developed a non-invasive murine OM model. In our model, adapted from a previously developed rat OM model, a pressure cabin is used in which a 40 kPa pressure increase is applied to translocate pneumococci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
(62 reference statements)
2
17
0
Order By: Relevance
“…Preliminary experiments showed that a pressure increase of 40 kPa delivered an intranasally administered inoculum to the middle ear (see Fig. S1 in the supplemental material), consistent with previous studies (20). The administration of inactivated Udorn/72 to the middle ear did not induce inflammation (Fig.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Preliminary experiments showed that a pressure increase of 40 kPa delivered an intranasally administered inoculum to the middle ear (see Fig. S1 in the supplemental material), consistent with previous studies (20). The administration of inactivated Udorn/72 to the middle ear did not induce inflammation (Fig.…”
Section: Resultssupporting
confidence: 85%
“…We then sought to assess if virus-induced middle ear inflammation was dependent on active viral replication. Udorn/72 was thus inactivated by ␤-propiolactone (BPL) treatment, and a pressure cabin system (20) was used to deliver the virus from the nasal cavity to the middle ear of 14-day-old mice. Preliminary experiments showed that a pressure increase of 40 kPa delivered an intranasally administered inoculum to the middle ear (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intranasal infection was performed as described above in the colonization model with the following exception: methylcellulose (1%) was added to the inoculum for all OM experiments in order to minimize leakage of inoculum to the lungs (67). Mice were placed in a supine position in the pressure cabin after infection as described previously (62). Briefly, an initial pressure rise was set at 10 kPa, and when the mouse started to regain consciousness and the first swallowing movements occurred, pressure was raised at the rate of 5 kPa per 15 s until a pressure of 40 kPa was reached, enabling the inoculum to reach the middle ear cavity.…”
mentioning
confidence: 99%
“…Groups of mice were sacrificed at 24, 48, and 96 h postinfection, where mice were bled out by retro-orbital puncture, followed by cervical dislocation. The bullas enclosing the middle ears (ME) were dissected from the temporal bone and homogenized in the presence of 1 ml sterile PBS per ear, as previously described (62,67). Bacteria were also recovered from the nasopharynx by performing an NPL using 1 ml of sterile PBS, and the lungs were extracted and homogenized in 2 ml sterile PBS.…”
mentioning
confidence: 99%